Impact of Silica Fume on the Strength Characterizes of Contaminated Soil - Mohamed M. Arbili; Mehmed Karpuzcu; Mohammed M. Ali (Polytechnic Journal)
In this paper a silica fume (SF) utilized as an admixture for improving the strength characterizes of contaminated soil and create new useful soils. Compaction test and direct shear test are used to evaluate the strength properties of clean and contaminated soil. Mixing SF with contaminated soil by crude oil is a rare study carried out. The strength characterizes of clean and polluted soil with crude oil was investigated. Three amount of light crude oil is combined with soils artificially in the percentage of 3%, 6%, and 9% by dry weight. However, three portions of SFs are used in the experimental work, which are 0%, 12%, and 18%. In the compaction test, results show that optimum moisture content (OMC) decreases with increasing degree of contamination, inversely while adding SF, OMC is increased. Maximum dry density dramatically decreased with an increasing amount of SF and crude oil. The shear strength properties enhance by utilizing SF where observed that the cohesion in clean soil is increased from 25.3 to 40.3 kPa and in contaminated soil by 9% crude oil is raised from 12.3 to 18.6 kPa so that SF can be rate as a successful material to enhance the soil properties.